A new method for unconstrained measurement of knee joint angle and timing in alpine skiing : comparison of crossover and crossunder turns - Chardonnens, J.; Favre, J.; Gremion, G.; Aminian, K. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Timing is an important part in the analysis of alpine skiing technique. Key events extracted from dynamics and kinematics of ski were previously proposed, but timing of body segments kinematics is also required to understand the biomechanics and to assess the performance. In this study, we proposed a new method based on inertial sensors to measure timing parameters based on body segments kinematics. To show the efficacy of the method, angle and timing of knee joints during crossover and crossunder techniques were compared. Significant differences were obtained for the timing, but not for the amplitude of the knee angles. The proposed system reported a good repeatability, did not encumber the athletes and allowed the measurement of body movement during the whole run. So it could easily be used to assess performance in training conditions.